2013
DOI: 10.1039/c3cc41645c
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent alteration of quorum sensing in Staphylococcus aureus

Abstract: Virulence in Staphylococcus aureus is strongly and positively correlated with local cell density. Here we present an effective approach to modulate this group behaviour using multivalent peptide-polymer conjugates. Our results show that by attaching multiple AIP-4' units to macromolecular scaffolds, the agr QS response in S. aureus was affected strongly, while displaying a clear multivalency effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…While only few studies have investigated AIP IV as a potential inhibitor of Agr, an interesting study by Yerushalmi et al showed that Agr group IV inhibition can be enhanced in the presence of an AIP IV macromolecule [81]. In that report, the authors conjugated up to 40 AIP IV molecules onto a polymer backbone scaffold using AIP IV monomers modified with a norleucine residue in place of the carboxyl methionine residue.…”
Section: Targeting S Aureus Agr Quorum-sensingmentioning
confidence: 99%
“…While only few studies have investigated AIP IV as a potential inhibitor of Agr, an interesting study by Yerushalmi et al showed that Agr group IV inhibition can be enhanced in the presence of an AIP IV macromolecule [81]. In that report, the authors conjugated up to 40 AIP IV molecules onto a polymer backbone scaffold using AIP IV monomers modified with a norleucine residue in place of the carboxyl methionine residue.…”
Section: Targeting S Aureus Agr Quorum-sensingmentioning
confidence: 99%
“…Yet for certain b-lactamases there appears to be a permissive correlation with particular bacteria, implying a fitness cost underlying the control of their expression (Fernández et al 2012). The biochemical basis for the much more complex transition from planktonic bacteria to the biofilm, as regulated by quorum-sensing pathways and correlated to virulence (Beceiro et al 2013), has revealed strategies -chemical (Morkunas et al 2012;Stacy et al 2012Stacy et al , 2013Imperi et al 2013b;Melamed Yerushalmi et al 2013;Saroj andRather 2013), biochemical (Chatterjee et al 2013), and microbiological ) -to interfere with this transition Hirakawa and Tomita 2013;Zhu and Kaufmann 2013). While the determination of the optimal structure and target for intervention is still uncertain (and is likely different for each bacterium), whole-genome analysis of the bacterial resistome (McArthur et al 2013) is a credible strategy to identify lineage in outbreaks Otto 2013b;Reuter et al 2013;Holt et al 2013); to identify resistance-evolution pathways (Abranches et al 2013;Kamen Ek and Gur-Bertok 2013;Méhi et al 2013); to correlate biochemical adaptation to resistance (as exemplified for daptomycin (Kelesidis et al 2013;Peleg et al 2012;Song et al 2013;Tran et al 2013); and to validate targets .…”
Section: Will An Understanding Of How Bacteria Recognize the Presencementioning
confidence: 97%
“…Antibacterial activity of the PDMS-based polymer particles with four concentrations of Ag-rGO (0, 0.5, 1, and 2 mL) was investigated against the bacterium Staphylococcus aureus (ATCC19095). All materials tested had dimensions of 0.5 cm × 1.0 cm and were sterilized with UV light [26]. All bacteria were stored at −80 ∘ C until required.…”
Section: Antibacterial Activitymentioning
confidence: 99%